GROWTH AND PRODUCTION OF MIMOSA LETTUCE USING WASTEWATER TREATED IN VERTICAL ANAEROBIC FILTERS - Leroy, Karl Auguste [UNESP]; Machado, Letícia Thália [UNESP]; Téllez, Hayver Olaya [UNESP]; Sánchez Román, E Rodrigo Máximo [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2022)
The present work aimed to investigate the response in field of the lettuce cultivar Gabi using treated sewage water in vertical anaerobic filters in different proportions. The study was carried out at the Department of Rural Engineering and Socioeconomics (DERS), Faculty of Agricultural Sciences (FCA) – São Paulo State University (UNESP), Botucatu-SP, in a completely randomized design, consisting of five treatments and five repetitions. The treatments were composed of five different compositions of the irrigation water depth prepared from two sources, one being tap water (AA) and another treated wastewater (ART), resulting in: T1 – 100%ART + 0%AA, T2-75%ART + 25%AA, T3-50%ART + 50%AA; T4-25%ART + 75%AA; T5 – 0%ART + 100%AA. Two lettuce cultivation cycles were carried out during the period from September to December 2021 and the results obtained were statistically analyzed. For the analyzed variables, a significant difference was found by the Tukey test at 5% probability between the treatments studied only for the dry mass during the first cultivation cycle, and the treatment T4 (25% ART + 75% AA) was that presented best result.
CRESCIMENTO E PRODUÇÃO DA ALFACE MIMOSA UTILIZANDO ÁGUA RESIDÚARIA TRATADA EM FILTROS ANAERÓBIOS VERTICAIS
Keywords: Lactuca sativa L; reuse; simplified treatment; sustainable agriculture